The entrepreneurial passion-entrepreneurial alertness relationship: the moderating role of a creative personality - Montiel-Campos, Héctor (Serbian Journal of Management, 2018)
Passion has been recognized as an important element in the field of entrepreneurship. However, we know little about the nature and effects of entrepreneurial passion. This research addressed this issue by exploring entrepreneurial passion as an antecedent of entrepreneurial alertness as well as the moderating effect of a creative personality in this relationship. Hypotheses were formulated from the literature review and they were tested on a sample of 406 individuals with primarily business backgrounds in 2016 in Mexico. Results suggested that individuals with a higher degree of entrepreneurial passion were more likely to show greater entrepreneurial alertness. However, creative personality as a moderating variable had minimal effects on this relationship. The main findings and implications of the obtained results, as well as the limitations and suggestions for future research in the field of entrepreneurship are discussed. Findings from this research suggest and encourage others to develop this research stream.